Is It Possible to Produce Certified Hazelnut Plant Material in Sicily? Identification and Recovery of Nebrodi Genetic Resources, in vitro Establishment, and Innovative Sanitation Technique From Apple Mosaic Virus - Yahyaoui, Emna; Marinoni, Daniela Torello; Botta, Roberto; Ruffa, Paola; Germanà, Maria Antonietta (Frontiers in Plant Science, 2021)
Eight Sicilian cultivars of hazelnut (Corylus avellana L.), namely-Curcia, Nociara Collica, Panottara Collica, Panottara Galati Grande, Parrinara, Panottara Baratta Piccola, Enzo, and Rossa Galvagno, registered into the Italian Cultivar Register of fruit tree species in 2017 were selected from Nebrodi area and established in vitro. The aim of the work was to carry out the sanitation of the cultivars and get virus-free plants from the most important viral pathogen threat, the apple mosaic virus. Virus-free plant material is essential for the production of certified plants from Sicilian hazelnut cultivars, complying the CE (cat. CAC) quality and the technical standards established in 2017 for voluntary certification by the Italian Ministry of Agricultural, Food and Forestry Policies (MIPAAF). In this study, we investigated the possibility of establishing in vitro true-to-type and virus-free hazelnut plantlets via the encapsulation technology of apexes. The in vitro shoot proliferation rates were assessed for the different cultivars, sampling periods, temperature treatments, and type of explant used for culture initiation. Viability, regrowth, and conversion rates of both conventional meristem tip culture (MTC) and not conventional (MTC combined with the encapsulation technology) sanitation techniques were evaluated.